Wide spectrum of presentation and variable outcomes of isolated left ventricular non-compaction. Issue 1 (27th April 2006) - Lofiego, C; Biagini, E; Pasquale, F; Ferlito, M; Rocchi, G; Perugini, E; Bacchi-Reggiani, L; Boriani, G; Leone, O; Caliskan, K; ten Cate, F J; Picchio, F M; et al.
Abstract : Objectives: To investigate diagnostic routes, echocardiographic substrates, outcomes and prognostic factors in patients with isolated ventricular non-compaction (IVNC) identified by echocardiographic laboratories with referral from specialists and primary care physicians. Patients and design: Since 1991, all patients with suspected IVNC were flagged and followed up on dedicated databases. Patients were divided into symptom-based and non-symptom-based diagnostic subgroups. Results: 65 eligible patients were followed up for 6–193 months (mean 46 (SD 44). In 53 (82%) patients, IVNC was associated with variable degrees of left ventricular (LV) dilatation and hypokinesia, and in the remaining 12 (18%) LV volumes were normal. Diagnosis was symptom based in 48 (74%) and non-symptom based in 17 (26%) (familial referral in 10). The non-symptom-based subgroup was characterised by younger age, lower prevalence of ECG abnormalities, better systolic function and lower left atrial size, whereas the extent of non-compaction was not different. No major cardiovascular events occurred in the non-symptom-based group, whereas 15 of 48 (31%) symptomatically diagnosed patients experienced cardiovascular death or heart transplantation (p = 0.01, Kaplan–Meier analysis). Independent predictors of cardiovascular death or heart transplantation were New York Heart Association class III–IV, sustained ventricular arrhythmias and left atrial size. Conclusions: IVNC is associated with a broad spectrum of clinical and pathophysiological findings, and the overall natural history and prognosis may be better than previously thought. Adult patients with incidental or familial discovery of IVNC have an encouraging outlook, whereas those who have symptoms of heart failure, a history of sustained ventricular tachycardia or an enlarged left atrium have an unstable course and more severe prognosis.